The sources of intentionality - Kriegel, Uriah (New York ; Oxford : Oxford University Press, 2011)
What do paintings, thoughts, words, desires, photographs, and perceptions have in common? They are all about something, are directed, are contentful - in a way chairs and trees, for example, are not. This book inquires into the source of this power of directedness that some items exhibit while others do not.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Intentionality (Philosophy)